Proximal Radioulnar Translocation Associated with Posterior Fracture–Dislocation of Elbow in an Adolescent Girl: A Case Report. Issue 1 (January 2020) - Samara, Eleftheria; Dayer, Romain; Davat, Marie; Ruffieux, Etienne; Steiger, Christina N.; Ceroni, Dimitri
Abstract : Case: A 14-year-old girl sustained a posterior elbow dislocation and presented with a proximal radioulnar translocation (PRUT) and a displaced fracture of the radial head. Reduction of the elbow dislocation and the proximal radioulnar translocation were achieved by external manipulation in the operating room. The radial head was not amenable to closed reduction and remained entrapped in the anteromedial compartment of the elbow. So open reduction and internal stabilization was carried out. Conclusions: In PRUT, closed reduction should be attempted. The radial head should be preserved even if it is fully dislocated from metaphysis. Retrograde intramedullary radial nailing provides enough stability of the fracture to promote early mobilization and facilitate union.